Transactional Maqaṣid al-Shariʿah as Framework to Ensure Legal Certainty in Digital Islamic Transactions - Nasrulloh, Muhammad; Ermawan, Mohamad Zakky Ubaid; Nabih, Muhammad Abdul Jawad; Hidayah, Ratu Bilqis Naily (IQTISHADIA, 2025)
This research originates from the widespread problems in contemporary digital transactions that have not been sufficiently addressed through studies of fiqh muʿāmalah or maqāṣid al-sharīʿah, indicating an urgent need for a theoretical framework capable of responding to the challenges of transactions in the digital era. Accordingly, this study offers the concept of Transactional Maqāṣid as a normative parameter to ensure that contractual practices remain within the bounds of sharia. Employing a library-based method with a conceptual approach and descriptive analysis, this study examines the relevance of maqāṣid al-sharīʿah to the dynamics of digital transactions, which are marked by information obscurity, vulnerability to fraud, and potential data manipulation. The findings demonstrate that Transactional Maqāṣid emphasize justice and certainty as foundational principles that produce mutual satisfaction (tarāḍī) among the parties, which is achieved by avoiding five elements that undermine transactional integrity: gharar, ghishsh, ribā, qimār, and ḍarar. To actualize these principles, Transactional Maqāṣid encourage enhanced transparency, documentation, and guarantees, all of which strengthen trust while providing higher levels of legal protection. Ultimately, this study concludes that the application of Transactional Maqāṣid in digital transactions provides legal certainty, reduces the potential for civil disputes, and ensures that sharia values remain relevant in the development of the digital economy.